JFQ volume 23 issue 1 Cover and Back matter (Journal of Financial and Quantitative Analysis, 1988)
The most modern introductory finance text available progresses from money and capital markets to portfolio theory, then to the firm and its financing and investing decisions. Separate, intuitive chapters on options, futures, and hedging strategies. International dimensions of finance integrated throughout. The most applications-oriented text available, with strong coverage of capital budgeting, plus the latest research on capital structure.